Implementation of User-Oriented Geovisualization Web Dashboard for Monitoring Access to Improved Water using Satellite Imageries Data - Fauzan Faldy Anggita; Arie Wahyu Wijayanto (Politeknik Statistika STIS, 2023)
This study aims to develop an engaging, web-based visualization dashboard for improved water access in Indonesia. The dashboard map was made using three technologies: the Qgis2web Python plugin for producing two-dimensional (2D) dashboard maps, JavaScript leaflets for map visualization, and Hypertext Markup Language (HTML), Cascade Stylesheet (CSS), and JavaScript for the user interface. The built-in map dashboard has several features, including grid click, legend, zoom, search, and measure distance, which are meant to help users determine the location of the nearest water treatment facilities, identify geographical features, and keep track of areas that have poor access to improved water. Evaluation using the system usability scale (SUS) concludes the dashboard is acceptable with an excellent rating. Our results reiterate and enhance support for government institution and relevant stakeholders in providing sustainable access to public water.